Investigating the shared genetic architecture between selective immunoglobulin A deficiency and autoimmune diseases - Xiao Dang; Frank Qingyun Wang; Caicai Zhang; Huidong Su; Yao Lei; Jing Yang; Yu Lung Lau; Wanling Yang (Human Genetics, 2026)
Selective immunoglobulin A deficiency (IgAD) is the most prevalent primary immunodeficiency and frequently coexists with autoimmune diseases (ADs), suggesting a shared genetic etiology. While genome-wide association studies (GWAS) have identified only a few risk loci for IgAD and hundreds for ADs, systematic cross-trait analyses are lacking, leaving the shared genetic architecture and underlying mechanisms poorly understood. In this study, we analyzed summary statistics from large-scale GWAS of IgAD and 10 common ADs. Cross-trait GWAS meta-analysis identified 51 pleiotropic loci significantly associated with IgAD and at least one AD (p < 5×10⁻⁸), 31 of which were novel for IgAD. Colocalization analysis further supported 33 shared loci between IgAD and ADs, including 19 novel IgAD loci, such as those near TNFAIP3 , CD28 , IRF4 , STAT4 , SH2B3 , APOBR and RAD51B . Gene-level analysis revealed shared pathways involved in T-cell differentiation and the intestinal immune network for IgA production. Tissue heritability analysis identified whole blood and the intestine as critical tissues, while single-cell RNA sequencing (scRNA-seq) highlighted B cell subtypes in the peripheral blood and gut as the most affected cell types in IgAD and ADs. Mendelian randomization further demonstrated bidirectional causal relationships between IgAD and several ADs. Our findings reveal a shared genetic architecture between IgAD and ADs, highlighting common functional mechanisms and providing insights into their biological interplay and potential immune-based therapies.